THE EFFECTIVENESS OF GOVERNMENT ASSISTANCE IN PROMOTING ECONOMIC INDEPENDENCE THROUGH MICRO ENTERPRISES IN CENTRAL LOMBOK, WEST NUSA TENGGARA PROVINCE - Harry Z Soeratin (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This study evaluates the effectiveness of government assistance in increasing economic independence through micro-enterprises in Central Lombok, West Nusa Tenggara. Involving 200 respondents selected through stratified random sampling, the study reveals that 70% of aid recipients experienced an average income increase of 30%, and 65% felt the aid helped them expand their business. Statistical analysis shows a significant positive correlation between the amount of aid and economic independence (correlation coefficient 0.65, p < 0.05). Factors influencing the effectiveness of aid include access to capital, skill training, bureaucracy, and lack of mentoring. These findings highlight the need for a more holistic approach and sustainable support to maximize the impact of government assistance.